The battle of Gettysburg, 1863 - Drake, Samuel Adams, 1833-1905 (Decisive events in American history., 2001)
The Battle of Gettysburg is Samuel Drake's recounting of one of the most famous battles of the Civil War. Drake brings you through the entire campaign, from the first march into Pennsylvania, to the final retreat of Lee and his forces. It is a brief but acute analysis and assessment of the encounter that brought about the end of the Confederacy. Book jacket.